دور التنظيم الاداري في تحقيق فعالية الادارة المحلية - - بن يطو نعمة (المسيلة, 2023)
ملخص: يعتبر التنظيم الإداري أداة رئيسية في تحقيق فعالية الإدارة المحلية ، يشمل التنظيم الإداري توزيع السلطات والمسؤوليات وتحديد الهيكل التنظيمي، و هدفه الأساسي هو خلق بيئة تشجع على التعاون والتنسيق وتحقيق الكفاءة والفعالية ، فهو يساعد في تحقيق الشفافية والمساءلة من خلال مراقبة الأداء وتقييم النتائج و ايضا حدد المسؤوليات والحدود المحددة للعمل والتفويضات المقررة لكل مستوى إداري حيث تركيزه يساهم في تحقيق الأهداف المحددة وتحسين الخدمات المقدمة للمواطنينيعتبر عنصرًا حيويًا في تحسين مستوى الحياة في المجتمعات المحلية وتحقيق التنمية و يساهم في تحقيق التعاون والتنسيق بين أفراد الإدارة المحلية فيحدد الأدوار والمسؤوليات والواجبات والحقوق لكل فرد داخل الإدارة المحلية و يسهم في تحديد الإطار الزمني للعمليات الإدارية وتحديد الأهداف والخطط والبرامج المطلوبة ، و تهدف هذه الدراسة إلى معرفة فعالية التنظيم الاداري في تحقيق الفعالية في الادارة المحلية على مستوى بلدية المسيلة. الكلمات المفتاحية:البلدية، التنظيم الإداري، بلدية مسيلة، فعالية التنظيم. Abstract Administrative organization is considered a key tool in achieving the effectiveness of local administration. It encompasses the distribution of authorities and responsibilities and the determination of the organizational structure. Its primary goal is to create an environment that encourages cooperation, coordination, efficiency, and effectiveness. It helps achieve transparency and accountability through performance monitoring and result evaluation, as well as defining responsibilities, boundaries, and delegations for each administrative level. Its focus contributes to achieving defined goals and improving services provided to citizens. It plays a vital role in improving the quality of life in local communities and achieving development. It also contributes to fostering cooperation and coordination among local administration members by defining roles, responsibilities, duties, and rights for each individual within the local administration. It aids in defining the timeframe for administrative processes and determining the required goals, plans, and programs. This study aims to examine the effectiveness of administrative organization in achieving efficiency in local administration at the municipality of M'Sila.
-دراسة ميدانية: بلدية المسيلة
Keywords: :البلدية، التنظيم الإداري، بلدية مسيلة، فعالية التنظيم.